Benefits and Challenges of Implementing Building Information Technology (BIM) in Industrialized Building System (IBS) Construction Project in Malaysia - WOO, XIANYANG; ANG SOON ERN, PENIEL (Progress in Engineering Application and Technology, 2021)
BIM offers new chances to improve the efficiency of IBS. BIM acts as a digital representation of constructed facility and offers an important line of ‘integration’ which is crucial in IBS. According to the recent research, researchers believe that BIM can lead to cost reduction and improve budgeting and cost estimating capabilities in IBS construction project. As an addition to its capabilities BIM has also has the potential to improve the designing process in IBS project. However, back to Malaysia, the development of construction industry in Malaysia are not looking up to expected which has the lowest contribution in economic productivity levels and adaption is needed in construction industry to make it up to expected. However, the implementation of BIM in IBS is relatively low since IBS contractors in Malaysia has difficulties such as technical problems, management, environmental issues, financial problems and legal issues in implementing BIM in IBS construction project. Hence, this research is aimed to identify the benefits of implementing BIM in IBS construction and investigate challenges of BIM implementation in IBS construction in Malaysia construction industry. A questionnaire survey was distributed to Grade 7 IBS contractors with BIM experience in Wilayah Kuala Lumpur and 44 respondents were received]. The data obtained was analyzed by frequency analysis by using SPSS software. Based on the results, the most agreed benefits are visualization of design, improve budgeting and cost estimating, monitoring and controlling cost and cash flow, installation process, and initial work process while the most agreed challenges of implementing BIM in IBS construction industry in Malaysia are high cost required for BIM training, high cost required for BIM experts and tools, lack of protection for intellectual property right, lack of insurance applicable to BIM implementation in IBS and lack of BIM standard.